ĐẶC ĐIỂM KHOÁNG VẬT QUẶNG TALC MỎ THU NGẠC, TỈNH PHÚ THỌ - Anh, Đào Duy; Thảo, Hoàng Thị Minh (Vietnam Journal of Earth Sciences, 2012)
Mineralogical characteristics of talc ore in Thu Ngac deposit, Phu Tho province Thu Ngac talc deposit has 8 ore bodies in which 5 bodies are considered as industrial scale. In the bodies TQ.1 and TQ.2, talc ore was mostly weathered but in the bodies TQ.3, TQ.4 and TQ.5, talc ore is original ore. These two ore types were collected and examined by AAS, XRD and especially HR-TEM methods. MgO makes up about 17.45 wt.% in the original ore and about 14.70 wt.% in the weathered ore. Talc as main mineral (approximately 50%), kaolinite/divermiculite/ montmorillonite mixed-layer mineral, halloysite, chlorite, quartz, hematite and anatase are encountered in the talc samples. In structure of the talc mineral, Mg can be isomorphous substituted by Fe mainly and Al. Structural chemical formulae of Thu Ngac talc are: Original ore: (Mg2,73Fe2+ 0,17Fe3+ 0,03Al0,04) (Si3,98Al0,02) O10(OH)2 Weathered ore: (Mg2,69Fe2+ 0,00Fe3+ 0,18Al0,08) (Si3,86Al0,14) O10(OH)2